Integration of Gender-sensitive Approach to Safe Motherhood Program for the Prevention of STD/ HIV in Iran: A Qualitative Study - Fatemeh Rahmanian; Masoomeh Simbar; Ali Ramezankhan; Farid Zayeri (Mashhad University of Medical Sciences, 2017)
Background & aim: Sexually transmitted infections (STIs) present a serious public health burden, which are considered as the factors contributing to acute illnesses, infertility, long-term disability, and mortality. The aim of the present study was to provide an in-depth understanding of the participants' perceptions about the integration of gender-sensitive approach to safe motherhood program for the prevention of STIs/human immunodeficiency virus (HIV) in Iran. Methods: This qualitative exploratory study was conducted on 32 male and female key informants, including health managers, health policy makers, and reproductive health providers. The participants were selected through the purposive sampling method, followed by the snowball sampling technique. The data collection was performed using the semi-structured interviews. The data were analyzed through the content analysis. Results: Based on the results, the participants' perceptions were categorized into two categories, namely the STIs/HIV prevention among males in safe motherhood and gender-sensitivity in primary maternal STIs/HIV prevention. Each of the patients was further divided into codes. The first category includes accountability to men's own sexual health needs' and prevention of ill-health effects of men on women's STIs/HIV status and the second category includes (1) condom negotiation skills in women (2) mandatory pre-marital HIV test policy, (3) partner notification guidelines, (4) STI/HIV risk assessment in safe motherhood services, and (5) women's right-based instruction for prenatal HIV screening in private services. Conclusion: As the findings of the present study indicated, the health policy makers were not adequately sensitive to gender sensitivity, which is particularly crucial for STIs/HIV prevention in the safe motherhood programs.